Community based surveillance for AMR monitoring: Significance, requirements and feasibility in LMICS - Afreenish Amir (South Centre, 2025)
Community based surveillance, in addition to clinical antimicrobial resistance (AMR) surveillance, plays an essential role in AMR and antimicrobial use trend monitoring. Various community-based AMR surveillance studies to monitor trends in AMR and use of antimicrobials have been conducted and shown its potential to facilitate evidence-based interventions and policy making for control of AMR. Many low and middle income countries (LMICs) lack the necessary systems and resources to establish effective surveillance systems. Specifically, the surveillance capacity at hospitals and other health facilities is limited, and the overall human resource capacity for community-level data collection, analysis, and multi-sectoral coordination is severely constrained. Prior to planning for community based AMR surveillance, a country should have established mechanisms to run the system efficiently, including strong governance and regulations, surveillance infrastructure, laboratory capacities, skilled human resources, data collection and management, funding and sustainability. The World Health Organization and quadripartite partners have recommended advancing community based AMR surveillance in LMICs, and integrated AMR surveillance combining information from humans, animals and ecosystems, which seems a challenge in the current situation. Considering the significant gaps in systems, resources, and capacities, it is important to prioritize strengthening the country's core capacities and addressing the underlying gaps in healthcare systems. Efforts should focus on enhancing the country's core capacities, systems, and technical requirements while exploring the potential of advancing selective community based AMR surveillance interventions and systems in the future.
Keywords: 300; AMR Surveillance; Antimicrobial Resistance (AMR); Community Based Surveillance; Health; Low- and Middle-income Countries (LMICs); Quadripartite; World Health Organization (WHO)